Pedigree of IAC sugarcane varieties: genetic vulnerability and need of a basic genetic improvement program - Pommer, Celso V.; Bastos, Cândido R. (Pesquisa Agropecuaria Brasileira, 2014)
The study of the pedigree of 23 IAC sugarcane varieties lead to the conclusion that only 3 species contributed to their formation: Saccharum officinarum, S. spontaneum and S. barberi. Co290 and POJ2878 were the outstanding varieties, being the ancestors of most IAC varieties, which caused a narrowed genetic base and therefore a genetic vulnerability to pests and diseases. The stablishment of a basic or broadening genetic program is discussed.